Green economy-based perspectives for sustainable economic growth - Alikulov Humayun Tohir oglu, (THE INNOVATION ECONOMY, 2026)
The article provides feedback on the prospects for the development of a green economy. It reflects models of green economy development, issues of efficient use of resources, principles of transition to a green economy. In particular, it was emphasized that the "green economy" is a model of economic development, an economy aimed at the efficient use of resources and ensuring social justice without harming the environment. This model is based on the following basic principles: energy efficiency: the use of renewable energy sources and reduction of energy consumption; resource management: sustainable management and processing of natural resources